2020
DOI: 10.1111/bioe.12824
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking ‘need’ for clinical support in transgender and gender non‐conforming children without clinical classification: Learning from ‘the paper I almost wrote’

Abstract: There have been ongoing debates as to how, or even whether, we should clinically classify gender diversity in children through clinical classification manuals. So‐called ‘depathologizing’ is argued as being vital to address the stigma that these children are somehow disordered or sick. Yet one argument in favour of continued clinical classification for transgender and gender non‐conforming children is that it better facilitates access to specialist psychological support. I argue that whilst continued clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…cit., 355 [167] (Thackray, Strickland and Murphy JJ). See also 359 [189] example, if parents, or medical professionals are unable to agree'. 103 The majority of the Court observed that in no stage 2 cases had 'contradictory evidence been forthcoming .…”
Section: Shifting Back From Court Involvementmentioning
confidence: 99%
“…cit., 355 [167] (Thackray, Strickland and Murphy JJ). See also 359 [189] example, if parents, or medical professionals are unable to agree'. 103 The majority of the Court observed that in no stage 2 cases had 'contradictory evidence been forthcoming .…”
Section: Shifting Back From Court Involvementmentioning
confidence: 99%
“… 33 This is not only problematic in and of itself but also, as Horowicz argues, limits therapeutic approaches, in that diagnostic criteria become individual symptoms to treat, limiting a holistic approach to the youth’s needs. 34 …”
Section: Critiques Of the Pathological Frameworkmentioning
confidence: 99%
“…33 This is not only problematic in and of itself but also, as Horowicz argues, limits therapeutic approaches, in that diagnostic criteria become individual symptoms to treat, limiting a holistic approach to the youth's needs. 34 Proponents of the pathological model may defend the current framework in that distress and dysphoria are not posited as inherent to trans identity, but rather a result of living within a transphobic society. Such an argument is disingenuous, given the frequent requirement of distress for access to GAC, especially in the case of youth, whose advocates rely heavily on justifications based in suicide prevention and mental illness.…”
Section: Impacts Of a Pathologized Approachmentioning
confidence: 99%